Letter from Paul Ziffren to Jane Tolmach - Paul Ziffren:::::: (1960)
A letter from Paul Ziffren to Jane Tolmach that invites Tolmach to attend a gala fundraising event where potential presidential nominees will be. The purpose of the Gala is to raise money by handing out dinner tickets.